The Effect of Substitution, Augmentation, Modification and Redefinition Model on Students’ Writing Skills - Binangbang, Jhurica (Middle Eastern Journal of Research in Education and Social Sciences, 2020)
Purpose: This study aimed to determine the effects of Substitution, Augmentation, Modification and Redefinition (SAMR) Model on Danao National High School Grade 12 students’ writing skills. Specifically, it sought to determine if SAMR Model could enhance the writing skills of students. Approach/Methodology/Design: The study only covered the writing skills which include ideas, organization, word choice, sentence fluency and convention (grammar and mechanics). The written outputs, specifically the rationale, significance of the study and scope and delimitation from the students’ Practical Research 2 subject were the bases for the experimentation. The study utilized quasi-experimental method to determine the effectiveness of Substitution, Augmentation, Modification and Redefinition Model as the basis for technology integration on enhancing the students’ writing skills. This study used the researcher-made pre-test and post-test questionnaire and raters were chosen to evaluate students’ outputs. Findings: It was found out that the level of the writing skills of the control and experimental groups did not change on their pre-test and post-test. Both groups showed an increase on their post-test results. The results of the experimental group indicated that SAMR Model has improved students’ writing skills Practical Implications: The utilization of this model on writing activities or subjects will likely create a new field of interest and widen students’ perspectives on the different means or medium of writing. However, this tool would really take much time, effort and technological skills on the part of the facilitator to make it as effective as possible. Originality/value: This study proposed Action Program to Improve Writing Instruction in Danao National High School.